2014
DOI: 10.1186/bf03353405
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic imaging of magma across the Narmada Son lineament, central India

Abstract: Wide band magnetotelluric (MT) studies were undertaken over a 130 km long, approximately north-south profile in central India across the Narmada Son lineament (NSL) that runs through Indian peninsula in ENE-WSW direction and its contiguous region. The NSL and its contiguous zone in the study region consists of Narmada graben, Satpura horst and Tapti-Purna graben, which are arranged from north to south as this order within the zone. The obtained deep crustal resistivity structure shows two deep-seated conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Hence, the information available from these sources may not be realistic solutions particularly to the complex zones concerning the source depth locations and delineation of specifics fault pattern (Kaila et al, 1989;Srivastava et al, 2007;Murty et al, Singh and Meissner, 1995;Bhattacharji et al, 2004;Verma and Banerjee, 1992;Rao et al, 2004;Singh, 1998;Waghmare et al, 2009;Nageswara Rao et al, 2011;Mishra 2011). The Euler deconvolution technique carried out in this area also correlated with the results of the workers as mentioned above and discussed in the text.…”
Section: Introductionmentioning
confidence: 54%
“…Hence, the information available from these sources may not be realistic solutions particularly to the complex zones concerning the source depth locations and delineation of specifics fault pattern (Kaila et al, 1989;Srivastava et al, 2007;Murty et al, Singh and Meissner, 1995;Bhattacharji et al, 2004;Verma and Banerjee, 1992;Rao et al, 2004;Singh, 1998;Waghmare et al, 2009;Nageswara Rao et al, 2011;Mishra 2011). The Euler deconvolution technique carried out in this area also correlated with the results of the workers as mentioned above and discussed in the text.…”
Section: Introductionmentioning
confidence: 54%
“…Patro and Sarma (2009) identified a two-layered lithospheric mantle structure of this region describing a highly-resistive nature of the lithospheric structure on the top, and a low resistive nature at the bottom. In addition, other studies by Naidu and Harinarayana (2009), Gokarn et al (2001), and Rao et al (2004) have identified anomalous conductive features at mid-lower crustal depths, through various factors such as partial melts, fluids, etc., in the same region. However, anomalous conductive features associated with significant seismicity is not discussed in detail in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Though several geophysical studies have been carried out earlier (Kaila et al, 1985;Verma and Banerjee, 1992;Singh and Meissner, 1995;Tewari and Prakash Kumar, 2003;Mall et al, 2005) including MT studies (Gokarn et al, 2001;Rao et al, 2004;Patro et al, 2005;Harinarayana et al, 2007;Naidu and Harinarayana, 2009) to understand the tectonic scenario of the lineament, the present study has been undertaken in order to add value to the earlier results. A major contribution from the present study is to understand the nature of the crust and mantle structure more clearly and also to examine the electrical signatures of the surface mapped faults such as the Narmada South Fault (NSF), Tapti Fault (TF), Gavligarh Fault (GF) and Purna Fault (PF), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The region recently experienced the 1997 Mw 5.8 Jabalpur earthquake, which occurred at the base of the Son-Narmada rift basin at a depth of *35 km in the lower crust through thrust dominated movement. The earthquake was followed by a few aftershocks, and their composite focal mechanism solution shows reverse faulting with left-lateral Strike-slip motion (BHATTACHARYA et al, 1997;RAMESH and ESTABROOK, 1998;SINGH et al, 1999;RAO and GUPTA, 2004). Isoseismal study for this earthquake carried out by the GSI indicates that the maximum intensity was estimated to be of VIII on the MSK scale and the worst affected village was Kosamghat, *20 km southwest of Jabalpur town.…”
Section: Historical Seismicity and The Seismogenic Sourcesmentioning
confidence: 99%